Assessment of the Ergonomic Quality of Hand-Held Tools and Computer Input Devices - Strasser, Helmut (IOS Press, 2013)
To this day, handymen and employees use tools and controls, i.e., hand-operated tools that are freely movable or in a fixed position. In order to avoid cumulative trauma disorders, work-related illnesses, or even occupational diseases especially during repetitive use, the tools must satisfy the equation “suitable for the human body = suitable for the hand.” That is, the aspect of compatibility in the basic ergonomic design must take the characteristics of the human hand-arm system, e.g., the motion ranges as well as the limits of the various joints, into consideration. Accordingly, a systematic ergonomic layout of the hand side of tools with respect to shape, dimensions, materials, and surface must be preceded by a thorough analysis that, for example, examines what needs to be performed with the tool under what conditions and how and where and with which type of grip and coupling it needs to be performed. The analysis as well as the subsequent design must always strive for holistic – rather than sectoral – goals in a systematic fashion and must consider interdependencies between the various design criteria. Several real-life examples in conjunction with evaluation studies to test the ergonomic quality of hand-held tools with electromyographic and subjective methods demonstrate the usefulness of such a systematic approach. It is furthermore helpful for the appropriate selection of truly ergonomically designed hand tools from an assortment of several variants